Involuntary changes in commuting distances: Effects on subjective well-being in the era of mobile internet - Katharina Bettig; Valentin Lindlacher (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Commuting is a fundamental aspect of employees' daily routines and continues to evolve with technological advancements. Yet the effects of commuting on subjective well-being remain insufficiently investigated in the context of expanding digital connectivity. This paper examines the causal effects of changes in commuting distance on subjective well-being in an era of widespread mobile internet availability. Exploiting exogenous shifts in commuting distance, we employ a Difference-in-Differences framework using data from the German Socio-Economic Panel (SOEP) from 2010 to 2019. Our results show that an involuntary increase in commuting distance reduces life satisfaction by 3 percent, on average, and heightens feelings of worry by almost 8 percent, on average. Our heterogeneity analysis shows that increased mobile coverage during commutes partially mitigates the decline in life satisfaction but exacerbates the negative impact on satisfaction with leisure.
Keywords: I31; J28; R40; 330; commuting; subjective well-being; mobile coverage; life satisfaction; SOEP; panel data